2011
DOI: 10.1002/pbc.22958
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PAX–FKHR fusion status in alveolar rhabdomyosarcoma: A report from the cooperative soft tissue sarcoma study group (CWS)

Abstract: PAX-FKHR fusion type was not a significant predictor for survival in our analysis. More extensive molecular analyses are needed to identify features with prognostic relevance and useful therapeutic impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 30 publications
2
60
1
Order By: Relevance
“…RMS are the most frequent soft tissue sarcomas in children with two main histologic subtypes, embryonal (ERMS) and alveolar (ARMS). The majority of ARMS are associated with PAX3-FOXO1 or PAX7-FOXO1 fusion genes and have generally more aggressive clinical behavior than ERMS (6)(7)(8)(9). PAX3-FOXO1 fusion protein has been shown to increase transcription of MYCN (10,11), although the prevalence of N-Myc protein expression and dependence on this in RMS has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…RMS are the most frequent soft tissue sarcomas in children with two main histologic subtypes, embryonal (ERMS) and alveolar (ARMS). The majority of ARMS are associated with PAX3-FOXO1 or PAX7-FOXO1 fusion genes and have generally more aggressive clinical behavior than ERMS (6)(7)(8)(9). PAX3-FOXO1 fusion protein has been shown to increase transcription of MYCN (10,11), although the prevalence of N-Myc protein expression and dependence on this in RMS has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aRMS is addicted to expression of the fusion protein as its continuous activity is essential for maintaining tumor cell survival (14,15). Finally, its presence has also important prognostic significance (16,17). PAX3-FOXO1 is, in conclusion, a highly relevant potential target and offers the opportunity for development of novel directed therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the expression of the fusion gene may provide additional biological properties to a subset of ARMS cases, despite the similar morphological characteristics by traditional histological examination. Furthermore, many studies have reported the prognostic impact of PAX3/7-FOXO1 fusion gene or its variants in ARMS, but it still remains a matter of debate [18][19][20][21][22][23][24][25][26][27][28][29]. A large multiinstitutional study by the International Society of Pediatric Oncology (SIOP) showed that the fusion positive ARMS contained statistically significant adverse prognostic factors for OS and event-free survival compared with the fusion negative ARMS and ERMS [27].…”
Section: Discussionmentioning
confidence: 97%
“…Using the predefined search strategy, we identified 163 potentially eligible articles, of which 69 were excluded due to duplication and 82 were excluded after reviewing the title and abstract (because of case reports; not original articles; not human subjects; not English language; not relevant to survival; primary visceral rhabdomyosarcoma). Finally, five studies were excluded after reviewing the complete article (because of partially duplicated patients; not used overall survival as outcome) [18][19][20][21][22]. A total of seven articles comprising 993 patients with RMS fulfilled all of the inclusion criteria [23][24][25][26][27][28][29].…”
Section: Literature Search and Selection Of Studiesmentioning
confidence: 99%